Transformasi Profesionalisme Guru PAI di Era Digital: Strategi Adaptif Menghadapi Tantangan Pendidikan Abad 21 - Diana, Diana; Rahman, Muhammad Hasbi Abdul (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2025)
The transformation of Islamic Religious Education (PAI) teachers’ professionalism in the digital era is an urgent strategic issue within the context of 21st-century education. This study aims to conceptually analyze the forms of professionalism transformation among PAI teachers, the challenges they encounter, and the adaptive strategies that can be implemented to address the dynamics of modern education. The method employed is library research by reviewing relevant journals, books, and policy documents. The analysis was conducted thematically across three main dimensions: strengthening professional competence, digital literacy, and the integration of Islamic values. The findings indicate that the transformation of PAI teachers must incorporate 21st-century competencies, particularly the 4Cs (critical thinking, collaboration, communication, and creativity), into pedagogical practices. Challenges such as technological gaps, limited training opportunities, and social complexities require contextual, collaborative, and value-based strategies rooted in Islamic principles. The contribution of this study lies in emphasizing a conceptual model for developing PAI teacher professionalism that is not only responsive to digital demands but also firmly grounded in spirituality, tawhid, justice, and trustworthiness. These findings are expected to serve as a reference for policymakers, educational institutions, and teacher communities in designing adaptive and sustainable professional development programs.